A Primer on Global Environmental Change. (20th November 2019) - Linnenluecke, Martina K.; Smith, Tom
Abstract : This paper sets out the science behind global environmental change, defined by the US Global Change Research Act as 'changes in the global environment (including alterations in climate, land productivity, oceans or other water resources, atmospheric chemistry, and ecological systems) that may alter the capacity of the Earth to sustain life'. We explain why there is still scepticism about the science in the business world and introduce eight gestalt shifts that are likely to change how executives think about environmental change and the threats and opportunities such changes present. The paper concludes with future research directions on business and global environmental change and outlines how the business case for investment in clean technology means that the transition to clean tech is inevitable.